Comparative transcription profiles of Candidatus Accumulibacter and Propionivibrio under phosphate limitation in sequencing batch reactors - Cardona, Laëtitia; Ramírez, Pilar Natalia Rodilla; Adler, Aline; Holliger, Christof (Frontiers in Microbiology, 2025)
Polyphosphate-accumulating organisms (PAOs) play a crucial role in enhanced biological phosphorus removal (EBPR) processes. In addition to biosynthesis, they rely on phosphate for energy generation. However, Candidatus Accumulibacter, a model PAO, has been shown to adapt to low phosphate conditions by switching to a glycogen-accumulating metabolism (GAM), with variable success across genus members and experiments. This study aimed to explore the metabolic shift of several Accumulibacter species subjected to low-phosphate concentration in different operating conditions using metatranscriptomics analysis. Furthermore, the study enabled a comparison of the transcriptomic profiles of Accumulibacter with those of Propionivibrio, a glycogen-accumulating organism typically found in EBPR plants. Two sequencing batch reactors were operated with different carbon sources to enrich for different populations of Accumulibacter. After decreasing the influent phosphate concentration, carbon removal performance was maintained while anaerobic phosphate release dropped dramatically, suggesting a shift from a phosphate-accumulating to a glycogen-accumulating metabolism. Analysis of metatranscriptomics data indicated that Accumulibacter regalis (type I) and Propionivibrio aalborgensis remained the most abundant species after the phosphate decrease in the reactor with acetate-propionate and allylthiourea, while Accumulibacter delftensis (type I) and Accumulibacter phosphatis (type II) remained active in the reactor with acetate-glucose and no allylthiourea. Transcription of the genes from the ethylmalonyl-CoA pathway involved in the production of propionyl-CoA and regulation of the anaerobic redox balance was enhanced under low-phosphate conditions, especially for type I Accumulibacter. Conversely, the transcription of the methylmalonyl-CoA pathway was enhanced under low-phosphate conditions in Propionivibrio and type II Accumulibacter.